Towards an ethnographic theory of excavation: encounters between native and academic theory on “the archaeological” in the Andes of Jujuy - Lema, Veronica (Instituto de Arqueología y Museo, Facultad de Ciencias Naturales e IML, Universidad Nacional de Tucumán, 2024)
An ethnographic theory is neither native nor academic theory, but the product of the encounter between both of them. This paper proposes taking the first steps in this direction in relation to the archaeological (which, despite being in the singular, refers to a multiplicity) in the Andes of Jujuy, Argentina, particularly in relation to excavation. From a situation during fieldwork where it was pointed out to me that my hands indicated that I do not work the land, I begin to wonder what it is -according to local eyes- what I do every time I excavate. Just as for them I don’t work the land, for me, they don’t dig; however, we engage in tasks that involve the subsoil and the ancients. We do not do the same, but we all do offerings before doing it. In fact, an [extra]ordinary event led me to reconsider what it is that I excavate. Throughout this work I will map these moments of connection and disconnection between native and academic theory, trying to open the archaeological, taking the excavation as reference, in order to reconsider aspects of the discipline and professional work.